Ultraviolet A/Riboflavin Collagen Cross-Linking for Treatment of Moderate Bacterial Corneal Ulcers. Issue 4 (April 2015) - Bamdad, Shahram; Malekhosseini, Hossein; Khosravi, Amir
Abstract : Purpose: To evaluate the therapeutic effect of UV-A/riboflavin collagen cross-linking (CXL) on moderate bacterial corneal ulcers. Methods: Thirty-two patients with moderate bacterial keratitis were selected. All patients were treated according to the standard medical treatment protocol. The patients were randomly allocated to 2 groups: case and control groups of 16 patients each using a numerical randomization table. The case group received CXL treatment. In the CLX group, corneal epithelium was removed and 0.1% riboflavin drops were applied. Then the corneas were irradiated with UV-A (365 nm) with an irradiance of 3 mW/cm 2 for 30 minutes. The grade of ulcers, size of epithelial defects, and area of infiltrates were recorded on days 1, 7, and 14 of treatment. Results: There was no statistically significant difference between the groups 1 day after the treatment. The mean treatment duration was 17.2 ± 4.1 days in the CXL group and 24.7 ± 5.5 days in the control group. The epithelial defects were smaller in the CXL group at 7 days ( P = 0.001) and 14 days ( P = 0.001) after the beginning of treatment. The area of infiltrates in CXL group was smaller than the control group at both 7 days ( P = 0.001) and 14 days ( P < 0.001) after the start of treatment. Conclusions: Our results support the beneficial effect of CXL in patients with moderate bacterial keratitis. In addition to accelerating epithelialization, this method shortens the course of treatment and may minimize or remove the need for surgery or other serious sequelae, such as corneal perforation.